Are Forced Turnovers Good or Bad News? - Axel Kind; Yves Schläpfer (University of Basel, Center of Business and Economics (WWZ), 2011)
To gain insights about the quality of board's firing decisions, we investigate abnormal stock returns and operating performance around CEO-turnover announcements in a new hand- collected sample of 208 “clean” turnover events between January 1998 and June 2009. Unlike the majority of previous studies, we show that forced turnovers do not per se represent a positive signal to hareholders. On the contrary, investors seem to critically assess the board's firing decision by considering the quality of the departing manager. When an outperforming CEO is dismissed or forced to leave - an event that occurs in as many as 35% of all dismissals in our sample - shareholders disesteem the board's decision. This finding is confirmed in multivariate cross-sectional regressions, holds for different time subperiods, and is robust to various event-test specifications and proxies of CEO quality.
Keywords: G14; G30; G34; 330; CEO turnover; Corporate governance; Firm performance; Führungskräfte; Kündigung; Führungskräfteauswahl; Corporate Governance; Unternehmenswachstum; Welt